Influencing Factors on the Increase of Child-rearing Households. (2017) - Andrade, Katia; Nakano, Hayato; Sugiki, Nao; Tamura, Toru
Abstract: Dealing with population decline and aging society is one the main challenges in Japan. The Japanese government aims to increase the quality of life of child-rearing households so as to ultimately increase birth rate and participation of females in the working market. Compact city policies and the Location Optimization Plan, recently proposed by the Government, are among the urban management measures adopted to support achieving this goal. Within this context, the purpose of the present research work is to investigate influencing factors on the increase of child-rearing households. Characteristics of child-rearing households in a local district of Sapporo city were explored, initially. Household micro data was estimated for the years of 1995 and 2010 by using Census data, Person Trip data as well as one available micro data simulation methodology. Analysis of the generated data showed that 25 of the total 90 Census zones presented an increase in the number of child-rearing households. Multiple Regression Analysis was then performed to explore the correlations between the increase in child-rearing households and factors related to building characteristics, land use types, and distance to urban facilities. Preliminary results suggest a negative correlation between the increase in child-rearing households and each of the building age, distance to elementary schools and commercial facilities. While it seems reasonable that newer buildings and shorter distances to schools (including nurseries) and supermarkets could help easing the daily activities of working parents, several other factors should be explored. The presented analysis can support government plans towards improving neighborhoods with a focus on child-rearing households, which in turn could help increase the birth rate and the number of two-worker households in Japan.